Peningkatan Prestasi Belajar Bahasa Arab dengan Metode Terjemah - Atik Wahyu Ningrum; Aisyah Hanun (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2023)
This study aims to determine the effect of learning the translation method on Arabic learning achievement. The subjects of this study were high school students Wahid Hasyim Sumberwudi Karanggeneng Lamongan. The type of research used is quantitative research which produces data and is analyzed by descriptive method. The data analysis technique used to determine whether there is an effective influence and the absence of an effective effect of learning the translation method on arabic learning achievement of sma wahid hasyim model students, the researcher uses the basic number product moment correlation formula. The results of the calculation of the product moment correlation formula between learning the translation method and arabic learning achievement of students of class xi sma wahid hasyim model can be obtained a value of rxy = 0.76 that the level of relationship between learning the translation method and learning achievement of arabic language students of class XI SMA Wahid Hasyim model is strong or high.